A Scientometxic Map Illustrating Sustainable Performance Through Bibliometric Analysis - Javaid, Zainab; Ilyas, Amina; Rahman, Saif Ur; Ali, Mubashar (iRASD Journal of Economics, 2023)
The field of sustainable performance (SP) research is expanding quickly, involving both industry and academia. In line with current developments in bibliometric research, the objective of this research is to map out the knowledge concerning the topic of sustainable performance (SP) and to identify current and future research trends. To present a detailed bibliometric study of the theoretical literature on SP reported in 202 articles between 2015 and 2022. This study identifies the most significant papers while presenting the key elements of the body of knowledge in this academic subject. It does this through the use of two sophisticated bibliometric visual software tools, Vos Viewer R studio, as well as the use of numerous bibliometric studies such as bibliographic coupling, co-citation and co-authorship analysis, and term co-occurrence, burst detection analysis, and timeline view analysis are all examples of bibliographic coupling. The paper concludes by discussing the utmost popular study subjects and suggesting recently developed research topics that scholars with an interest in SP should put on their future research agenda. This paper presents the findings of a bibliometric investigation on performance measurement systems and sustainability, with a focus on industrial systems. The findings point to a misalignment between performance assessment and sustainability.